The Role of the TRPV4 Channel in Intestinal Physiology and Pathology - Liu D; Mao M; Liu W; Xie L; Zhong X; Cao W; Chen L (Journal of Inflammation Research, 2024)
Dandan Liu,1,* Mingli Mao,1,* Wenjia Liu,1 Lihua Xie,1 Xiaolin Zhong,1 Wenyu Cao,2 Ling Chen1 1Department of Metabolism and Endocrinology, The First Affiliated Hospital of University of South China, Hengyang Medical School, University of South China, Hengyang, Hunan, 421001, People’s Republic of China; 2Clinical Anatomy & Reproductive Medicine Application Institute, Hengyang Medical School, University of South China, Hengyang, Hunan, 421001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ling Chen, The First Affiliated Hospital of University of South China, Department of Endocrinology and Metabolism, Hengyang Medical School, University of South China, Hengyang, Hunan, 421001, People’s Republic of China, Email lingchen-cl@outlook.comAbstract: The transient receptor potential vanilloid 4 channel (TRPV4) is an important member of the TRP superfamily of cation channels. The channel can be activated by different physical and chemical stimuli, such as heat, osmotic, and mechanical stress. It regulates the release of nociceptive peptides (substance P and calcitonin gene-related peptide), and mediates neurogenic inflammation, which indicates the involvement of TRPV4 as a nociceptor. Previous studies show that TRPV4 regulates the contraction of intestinal smooth muscle, mucosal barrier permeability, intestinal ion transport, activation of submucosal enteric neurons, and generation of immune cells. TRPV4 is involved in various pathophysiological activities, and altered TRPV4 expression has been detected in some intestinal diseases (IBD, IBS, intestinal tumors, etc). Evidence indicates that TRPV4 plays a noxious role in intestinal barrier function when the intestine is damaged. This review focuses on the role of the TRPV4 channel in the physiological and pathological functions of the intestine, and evaluates the potential clinical significance to target TRPV4 channel in the treatment of intestinal diseases.Plain Language Summary: TRPV4 is expressed in the intestine and regulates intestinal functions, such as intestinal barrier function, gastrointestinal motility, sensory transduction, and intestinal ion transport. It is upregulated in most intestinal disease models and participates as a negative regulator. TRPV4 inhibition is a potential treatment for intestinal diseases. TRPV4 antagonists also show a positive protective effect on intestinal related diseases. The activation or inhibition of TRPV4 in the treatment of different intestinal diseases has put forward a feasible research direction in the future.Keywords: TRPV4, intestinal diseases, gastrointestinal motility, sensory transduction